Orientation and Basis of Educational Management in a Pedagogical Perspective - Sania Cahyani; Yaya Sunarya (al-Afkar, Journal For Islamic Studies, 2025)
This research covers three main aspects of educational management, namely orientation, basis, and pedagogical perspective. This research aims to identify problems in these three aspects and find the best solution through the final results. The research method used is descriptive qualitative by analyzing various relevant library sources. The research results reveal that the goal orientation of educational management involves careful integration to achieve educational success by paying attention to mission, background, scenarios, resources, and feedback. Meanwhile, the results of educational management are related to the measurable achievement of students' knowledge and skills. The basic education management process includes seven steps, namely planning, organizing, workforce placement, directing, coordinating, reporting, and funding. Meanwhile, Total Quality Management (TQM) is important in ensuring continuous improvement by involving all parties in efforts to increase customer satisfaction and overall quality through its implementation. Meanwhile, educational management from a pedagogical perspective includes five aspects, namely learning theory, curriculum development, guidance, educational management, and evaluation of learning outcomes. The conclusions in this research confirm that the pedagogical perspective provides a very useful basis for improving the quality of educational management through goal and outcome orientation as well as the process basis of education management and Total Quality Management (TQM) that is applied.